Adherence to Antihypertensive Treatment and the Blood Pressure–Lowering Effects of Renal Denervation in the Renal Denervation for Hypertension (DENERHTN) Trial. Issue 12 (20th September 2016) - Azizi, Michel; Pereira, Helena; Hamdidouche, Idir; Gosse, Philippe; Monge, Matthieu; Bobrie, Guillaume; Delsart, Pascal; Mounier-Véhier, Claire; Courand, Pierre-Yves; Lantelme, Pierre; Denolle, Thierry; Dourmap-Collas, Caroline; et al.
Abstract : Background: The DENERHTN trial (Renal Denervation for Hypertension) confirmed the blood pressure–lowering efficacy of renal denervation added to a standardized stepped-care antihypertensive treatment for resistant hypertension at 6 months. We report the influence of adherence to antihypertensive treatment on blood pressure control. Methods: One hundred six patients with hypertension resistant to 4 weeks of treatment with indapamide 1.5 mg/d, ramipril 10 mg/d (or irbesartan 300 mg/d), and amlodipine 10 mg/d were randomly assigned to renal denervation plus standardized stepped-care antihypertensive treatment, or the same antihypertensive treatment alone. For standardized stepped-care antihypertensive treatment, spironolactone 25 mg/d, bisoprolol 10 mg/d, prazosin 5 mg/d, and rilmenidine 1 mg/d were sequentially added at monthly visits if home blood pressure was ≥135/85 mm Hg after randomization. We assessed adherence to antihypertensive treatment at 6 months by drug screening in urine/plasma samples from 85 patients. Results: The numbers of fully adherent (20/40 versus 21/45), partially nonadherent (13/40 versus 20/45), or completely nonadherent patients (7/40 versus 4/45) to antihypertensive treatment were not different in the renal denervation and the control groups, respectively ( P =0.3605). The difference in the change in daytime ambulatory systolic blood pressure from baseline to 6 months between the 2 groups was –6.7 mm Hg ( P =0.0461) in fully adherent and –7.8 mm Hg ( P =0.0996) in nonadherent (partially nonadherent plus completely nonadherent) patients. The between-patient variability of daytime ambulatory systolic blood pressure was greater for nonadherent than for fully adherent patients. Conclusions: In the DENERHTN trial, the prevalence of nonadherence to antihypertensive drugs at 6 months was high (≈50%) but not different in the renal denervation and control groups. Regardless of adherence to treatment, renal denervation plus standardized stepped-care antihypertensive treatment resulted in a greater decrease in blood pressure than standardized stepped-care antihypertensive treatment alone. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01570777. Abstract : Supplemental Digital Content is available in the text.